Book review: Jenia Mukherjee, Blue Infrastructures: Natural History, Political Ecology, and Urban Development in Kolkata. (November 2022) - Dahake, Shilpa
Jenia Mukherjee, Blue Infrastructures: Natural History, Political Ecology, and Urban Development in Kolkata . Singapore: Springer, 2020, 239 pp. ₹4, 123.25. ISBN: 978-981-15-3951-0.